Are External Magnetic Disturbances Suppressed by Magnetometer Noise when Estimating a Nanosatellite's Rotational Motion?. Issue 2 (2020) - Cilden-Guler, Demet; Kaymaz, Zerefsan; Hajiyev, Chingiz
Abstract: In this study, a three-axis magnetometer based attitude estimation algorithm that includes external magnetic field model is presented. The magnetic fields from the external sources are considered in the geomagnetic field model used in the attitude estimation algorithm and not treated as error sources on the magnetometer. By this way, it was aimed to model the magnetometer better by taking into account the effects of the space environment and perform a higher accuracy in the estimation of the rotational motion of the satellite. However, a problem arose such that the magnetometer sensor noise levels used in the attitude estimations appear to mask the effects of the external magnetic field. The fact that with the developing technologies in micro-electro-mechanical systems, the magnetometer noise might be keep decreasing, led us to investigate the magnitude of the noise level that would suppress the external field.